2018
DOI: 10.1039/c7se00511c
|View full text |Cite
|
Sign up to set email alerts
|

Solvent induced surface modifications on hydrogen storage performance of ZnO nanoparticle decorated MWCNTs

Abstract: Surface functionalization via decorating nanometal particles on MWCNTs for hydrogen uptake through a spillover mechanism is the key for hydrogen energy storage for transport sectors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The preparation of the AlH 3 •TEDA and its subsequent decomposition to Al and TEDA in Fig. 8 illustrates the reversibility of the reaction ( 12 ). It was calculated that the H f and S for the reaction ( 12 ) are [129] suggested that the amount of Ti needed to catalyze the activity of Al is on the order of 0.4 at.%, which is significantly lower than the originally added.…”
Section: Regeneration Using Alh 3 Adductsmentioning
confidence: 97%
See 1 more Smart Citation
“…The preparation of the AlH 3 •TEDA and its subsequent decomposition to Al and TEDA in Fig. 8 illustrates the reversibility of the reaction ( 12 ). It was calculated that the H f and S for the reaction ( 12 ) are [129] suggested that the amount of Ti needed to catalyze the activity of Al is on the order of 0.4 at.%, which is significantly lower than the originally added.…”
Section: Regeneration Using Alh 3 Adductsmentioning
confidence: 97%
“…Fig. 9 shows the hydrogen absorption and desorption isotherms at 88 °C for reaction ( 12 ). The preparation of the AlH 3 •TEDA and its subsequent decomposition to Al and TEDA in Fig.…”
Section: Regeneration Using Alh 3 Adductsmentioning
confidence: 99%
“…They are good solvents for many substances. 25,26 Inorganic salts are difficult to dissolve in organic solvents, but Mg(ClO 4 ) 2 is soluble in N,N-dimethylformamide and acetonitrile organic solvents. 27 Therefore, Mg(ClO 4 ) 2 was selected as an ionophore to transport Mg 2+ .…”
Section: Mg + 2h 2 O / Mg(oh) 2 + Hmentioning
confidence: 99%
“…These properties are the features that distinguish hydrogen energy from other energy sources. [7][8][9] Hydrogen spillover is an approach to be considered to enhance hydrogen storage in carbon nanostructure intercalation onto metal catalyst (like, Ni,Co, Pt, and Pd) supported carbon nanotubes that enhanced hydrogen storage properties. [10][11][12] Hydrogen molecules dissociate to atomic hydrogen on a metal catalyst and subsequently migrate from the metal to surface of CNTs.…”
Section: Introductionmentioning
confidence: 99%